The Influence of Social Media Engagement, Customer Experience, and Brand Reputation on Digital Brand Trust of Mobile Banking Users - Sri Purwati; Sukma Irdiana; Ade Suhara; Iwan Henri Kusnadi; Rahmat Irawan; Nur Aisyah Qadri Saiful (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The purpose of this research is to examine Effect of Social Media Engagement, Customer Experience and Brand Reputation on Digital Brand Trust of mobile banking customers. The research was conducted quantitatively utilizing a survey method on mobile banking customers by employing purposive sampling methodology. Data collection was done by means of online surveys and data analysis was done using multiple linear regression. Before assessing the hypothesis, validity, reliability and classical assumption tests such as normality, heteroscedasticity and multicollinearity were undertaken. The findings indicated that Social Media Engagement, Customer Experience and Brand Reputation had a favorable and substantial effect on Digital Brand Trust partly and concurrently. The study results show that enhancing customer involvement via social media, great customer experience and strong brand reputation may boost consumer confidence in mobile banking services. The research contributes to the growth of digital marketing and consumer behavior literature theoretically, and the practical implications for the banking sector to increase customer confidence in digital services.